Zend Framework 2.0 by example beginner's guide - Shasankar, Krishna (Birmingham, UK : Packt Publishing Ltd., 2013)
Annotation aster application development with Zend Framework 2.0Learn about Zend Framework components and use them for functions such as searching, image processing, and payment gateway integrationsIntegrate third-party services for media sharing and payment processing.
Includes index.
Description based on print version record.
Keywords: COMPUTERS / Programming / Open Source; COMPUTERS / Software Development & Engineering / General; COMPUTERS / Software Development & Engineering / Tools; Web site development; PHP (Computer program language); Application software -- Development; Electronic books